MeNPF4.5 Improves Cassava Nitrogen Use Efficiency and Yield by Regulating Nitrogen Uptake and Allocation - Liang, Qiongyue; Dong, Mengmeng; Gu, Minghua; Zhang, Peng; Ma, Qiuxiang; He, Bing (Frontiers in Plant Science, 2022)
Improving nitrogen use efficiency (NUE) is a very important goal of crop breeding throughout the world. Cassava is an important food and energy crop in tropical and subtropical regions, and it mainly use nitrate as an N source. To evaluate the effect of the nitrate transporter gene MeNPF4.5 on the uptake and utilization of N in cassava, two MeNPF4.5 overexpression lines (MeNPF4.5 OE-22 and MeNPF4.5 OE-34) and one MeNPF4.5 RNA interference (RNAi) line (MeNPF4.5 Ri-1) were used for a tissue culture experiment, combining with a field trial. The results indicated that MeNPF4.5 is a plasma membrane transporter mainly expressed in roots. The gene is induced by NO3−. Compared with the wild type, MeNPF4.5 OE-22 exhibited improved growth, yield, and NUE under both low N and normal N levels, especially in the normal N treatment. However, the growth and N uptake of RNAi plants were significantly reduced, indicating poor N uptake and utilization capacity. In addition, photosynthesis and the activities of N metabolism-related enzymes (glutamine synthetase, glutamine oxoglutarate aminotransferase, and glutamate dehydrogenase) of leaves in overexpression lines were significantly higher than those in wild type. Interestingly, the RNAi line increased enzymatic activity but decreased photosynthesis. IAA content of roots in overexpressed lines were lower than that in wild type under low N level, but higher than that of wild type under normal N level. The RNAi line increased IAA content of roots under both N levels. The IAA content of leaves in the overexpression lines was significantly higher than that of the wild type, but showed negative effects on that of the RNAi lines. Thus, our results demonstrated that the MeNPF4.5 nitrate transporter is involved in regulating the uptake and utilization of N in cassava, which leads to the increase of N metabolizing enzyme activity and photosynthesis, along with the change of endogenous hormones, thereby improving the NUE and yield of cassava. These findings shed light that MeNPF4.5 is involved in N use efficiency use in cassava.